Contributions of Marxist feminism to think about the Argentine feminist and women's movement in the face of neoliberal rationality:: a reading by Silvia Federici and Rita Segato - Romano Roth, Carla (Universidad Nacional de Villa María, 2019)
We attend to a moment of relegitimity of the neoliberal order, particularly linked to policies of adjustment of the States or, from other perspectives, to a neoliberal rationality that extends the market to all spheres of life, making the neoliberal homo economicus a central figure. At the same time, we observe popular resistances to this logic of the world, where the struggles of the women and feminist’s movement of Argentina of recent years can be located, particularly after its massification with the first mobilization Ni Una Menos of 2015. In this work, I inquire about the contributions that two marxist feminist authors, such as Silvia Federici and Rita Segato, can make to think of the argentine feminine and feminist activisms of recent times in a context of discursive hegemony of neoliberal rationality. While the first, from a review of Marx's work with feminist lenses, exposes the centrality of reproductive work, the second, from an anthropological and feminist perspective, in a context of ownership, sustains the importance of practising a links’ politics in feminine key.